Relations between IT Architecture and Information Quality in DW and BI Environments - Schmidt, Samuel Otero; Prado, Edmir P. Vasques; Takaoka, Hiroo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2012)
The organizations are investing more in information technology to collect, store and process vast amounts of information. Generally this information has no standard and repeated data, which hinders the decision making process. The cause of the difficulties is related to Information Quality (IQ) that has technical characteristics related to the architecture used in Data Warehouse (DW) and Business Intelligence (BI) environments. Based on the existing literature and insights from the author a research model was created to identify the relations between components of DW/BI architecture and IQ dimensions. We used the case study as research method. This research makes contributions to better understand IT architecture for DW/BI.